Dynamic power service restoration method for distribution network with distributed generation penetration. (December 2020) - Niu, Geng; Wei, Xuteng; Wu, Ming; Kou, Lingfeng; Lin, Jianhua; Li, Yijin
Abstract: In this paper, a dynamic power service restoration method for the distribution network with DG is proposed. The mathematical model of the power service restoration problem is analyzed and established. Based on the mathematical model, a two-stage dynamic power service restoration strategy is developed. In the proposed method, the initial power service restoration scheme can be obtained by solving the optimal model in the first stage. Then, the power service restoration scheme can be adjusted and updated according to the actual DG output power periodically by the rolling strategy in the second stage. The correctness and effectiveness of the proposed method are verified by a MATLAB simulation based case study. The computing speed of the proposed method is fast, which makes it have good practical application values and prospects.